2011
DOI: 10.1186/1476-069x-10-35
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency hearing loss, occupational noise exposure and hypertension: a cross-sectional study in male workers

Abstract: BackgroundThe association between occupational noise exposure and hypertension is inconsistent because of an exposure bias caused by outer-ear measurements of noise levels among workers. This study used hearing loss values (HLVs) measured at 4 kHz and 6 kHz in both ears as a biomarker to investigate the chronic effects of noise exposure on hypertension in 790 aircraft-manufacturing workers.MethodsParticipants were divided into a high hearing loss (HL) group (n = 214; average HLVs ≥ 30 decibel [dB] at 4 kHz or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 32 publications
6
41
0
12
Order By: Relevance
“…times greater prevalence of CVD, such as hypertension (130). Other findings strongly support the theory that noise exposure has an impact on hypertension, and some data suggest that hearing loss and hypertension severity is associated (131)(132)(133). As such, this cross-sectional data supports the need for further evaluation of noise and CVD.…”
Section: Example 23supporting
confidence: 63%
“…times greater prevalence of CVD, such as hypertension (130). Other findings strongly support the theory that noise exposure has an impact on hypertension, and some data suggest that hearing loss and hypertension severity is associated (131)(132)(133). As such, this cross-sectional data supports the need for further evaluation of noise and CVD.…”
Section: Example 23supporting
confidence: 63%
“…This finding is consistent with the results of chang et al, who found that noise-induced hearing loss at high frequency was significantly associated with hypertension even after controlling for potential confounders using multivariate logistic regression analysis 23 Also, in our final multivariate model, other co-variables such as age, smoking and positive family history were independently associated with high blood pressure. These co variables are established risk factors for high blood pressure in the biomedical literature 42-43…”
Section: Resultssupporting
confidence: 82%
“…This was inconsistent with zawilla et al found no association between hypertension and hearing impairment or noiseinduced hearing loss (NIHL) 33 However, our result were consistent with a field study that reported significantly higher means of systolic blood pressure (SBP) and diastolic blood pressure (DBP) in workers with an auditory impairment ≥ 65 dB at 3, 4, or 6 kHz compared with those with normal hearing 24 . Similarly, chang et al reported that there was a significant difference between high hearing loss workers and the low hearing loss workers in the prevalence of hypertension, as 43.5% of the high level hearing loss workers had hypertension compared to only 33.2% of the low Hearing Loss workers 23 . Another study confirm our findings, as it reported a statistically significant prevalence of hypertension and electrocardiographic abnormalities among workers exposed to noise with audiometric deficit compared to workers exposed with normal hearing 34 .…”
Section: Resultsmentioning
confidence: 99%
“…A conveniência de uma amostra impossibilita fazer uso da inferência estatística dos resultados, já que ela não foi obtida atendendo aos pressupostos da estatística inferencial. Da mesma forma, em caso de estudos que abordam o universo de indivíduos (um censo) [5][6]10,12,25 não há porque se fazer testes estatísticos, tendo em vista que os resultados foram obtidos para todos os indivíduos da população e, portanto, não foi retirada uma porção de um universo para o qual pretende-se inferir estatisticamente os resultados obtidos na amostra.…”
Section: Discussionunclassified
“…Todos os oito estudos [5][6][7][8][9][10][11][12] retidos sobre ruído e hipertensão demonstraram alguma associação positiva, inclusive aqueles que foram analisados em combinação com outros fatores de risco ocupacionais (trabalho em turnos e solventes) 5,8,11 . No entanto, os resultados encontrados são variáveis com relação aos seguintes aspectos: medida de frequências de ruído, nível em decibéis e alteração de pressão sistólica e/ou diastólica.…”
Section: Ruídounclassified